Why Gen Z Loves Rucas: The Role of Self-Congruence, Brand Authenticity, and Brand Satisfaction in Building Brand Love - Zuliyono, Tighanda Putra; Sekarsari, Larasati Ayu (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2025)
Purpose of this study is to examine the influence of self-congruence, brand authenticity, and brand satisfaction on brand love for the local fashion brand Rucas among Generation Z. Methodology This study employs a quantitative method with primary data collected through an online survey using Google Forms. The respondents in this research consist of Generation Z consumers aged 19–27 years who reside in Surabaya and use Rucas brand products. The study adopts a purposive sampling technique with a total sample of 205 respondents. Data analysis is conducted using the WARPLS version 7.0 software, employing both descriptive and statistical analysis approaches. Findings The results of the study indicate that self-congruence has a significant effect on brand love and brand satisfaction. Additionally, brand authenticity has also been shown to significantly influence both brand satisfaction and brand love. Brand satisfaction significantly affects brand love. Suggestions include expanding the population and sample to encompass more local fashion brands and adding other variables, such as brand loyalty, to enrich the analysis of consumers' emotional relationships with brands